Determination of optimal conditions for pressure oxidative leaching of Sarcheshmeh Molybdenite concentrate using Taguchi method - Khoshnevisana A.; Yoozbashizadeha H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The present research work is based on finding the optimum conditions for pressure oxidative leaching of the molybdenite concentrate to produce technical-grade molybdic oxide (MoO3) with high recovery through further treatment of the filtrate solution. The Taguchi method was used to design and minimize the number of experiments. By using Taguchi orthogonal (L25) array, five parameters (time, temperature, oxygen pressure, pulp density and acid concentration) at five levels were selected for 25 experiments. The experiments were designed and carried out in a high-pressure reactor in the presence of nitric acid as solvent and oxidizing agent for the molybdenite concentrate and its ReS2 content. The optimum conditions for pressure leaching of molybdenite were obtained through using Signal to Noise analysis and modified by using Minitab software prediction tool. Furthermore, the optimum condition for an economical pressure leaching of rhenium sulfide (ReS2) was achieved with the same process. Analysis of variance (ANOVA) showed that the pulp density is of paramount importance in this process.